IMPLEMENTASI BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK PADA PESERTA DIDIK DI SEKOLAH MENENGAH KEJURUAN NABIL HUSEIN - Imas Sri Sukmawati (UNISAN JURNAL, 2024)
This study aims to investigate the role of guidance and counseling teachers in fostering student morals at SMK Nabil Husein Samarinda . Guidance and counseling teachers have an important responsibility in assisting students in the development of good morals. This research uses a qualitative approach with a case study method. Data was collected through participatory observation, in-depth interviews, and analysis of documents related to the guidance and counseling program in schools. The results of this study indicate that the guidance and counseling teacher’s role is very significant in fostering student morals. Guidance and counseling teachers are involved in the process of developing student morals through various activities, such as counseling, individual counseling, group counseling, and class program development. They help students understand the principles of good morals, reinforce moral values, and develop students’ social skills. In addition, counseling guidance teachers also act as companions and motivators for students. They provide emotional and psychological support to students, help them deal with conflicts and challenges in everyday life, and provide constructive advice. The findings of this study also show that a holistic and integrated approach to counseling is very important in fostering student morals. Counseling teachers work closely with teachers and parents to create an educational environment that supports the overall moral development of students. This research contributes to an understanding of the important role of guidance and counseling teachers in fostering student morals at SMK Nabil Husein Samarinda . The results of this study are expected to provide input for the development of guidance and counseling programs in other schools to improve student moral development.